"Westerman Tables for the Metal Trade: Materials, Numerical Quantities, Forms" - Jutz (Hermann); Scharkus (Eduard) (1990)
Metal Trade ; Materials ; Numerical Quantities ; Forms
Keywords: Metal Trade ; Materials ; Numerical Quantities ; Forms